2020
DOI: 10.3390/ijms21239280
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Molecular Processes and Genetic Architecture Underlying Iron and Zinc Homeostasis for Biofortification: From Model Plants to Common Wheat

Abstract: The micronutrients iron (Fe) and zinc (Zn) are not only essential for plant survival and proliferation but are crucial for human health. Increasing Fe and Zn levels in edible parts of plants, known as biofortification, is seen a sustainable approach to alleviate micronutrient deficiency in humans. Wheat, as one of the leading staple foods worldwide, is recognized as a prioritized choice for Fe and Zn biofortification. However, to date, limited molecular and physiological mechanisms have been elucidated for Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 200 publications
3
34
0
Order By: Relevance
“…Gorafi et al ( 32 ) identified a significant and positive phenotypic correlation between GZn and GFe ( r = 0.78) and a pleiotropic QTL on chromosome 5D; significant and positive correlations between GZn and GFe were also found in other studies ( 11 , 42 ). It has been reported that some transporters, chelators, and genes regulated GZn and GFe simultaneously in a high frequency ( 10 , 43 ). These findings indicated that Zn and Fe could be improved simultaneously in breeding programs targeting mineral biofortification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorafi et al ( 32 ) identified a significant and positive phenotypic correlation between GZn and GFe ( r = 0.78) and a pleiotropic QTL on chromosome 5D; significant and positive correlations between GZn and GFe were also found in other studies ( 11 , 42 ). It has been reported that some transporters, chelators, and genes regulated GZn and GFe simultaneously in a high frequency ( 10 , 43 ). These findings indicated that Zn and Fe could be improved simultaneously in breeding programs targeting mineral biofortification.…”
Section: Discussionmentioning
confidence: 99%
“…Fe deficiency in humans most commonly leads to nutritional anemia in women and children ( 8 ). Therefore, it is very important to improve the nutritional quality of wheat by enhancing the Zn (GZn) and Fe (GFe) concentrations in grain ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-nine (Raney et al 2013;Andersson et al 2017;Bouis et al 2020) marker trait associations were identified for Zn on chromosomes 2 and 7 (Velu et al 2018b). As Fe and Zn concentration of crops is controlled by a large number of loci, it is currently challenging to implement the findings in breeding programs, so more precision is required to discover the exact regions responsible for Fe and Zn concentration and to give an indication of variation in these markers and their potential effectiveness in breeding (Tong et al 2020). The complete haplotype-block based method could be more effective and practical (Ali and Borrill 2020).…”
Section: Molecular Markersmentioning
confidence: 99%
“…To improve our understanding of the genetic basis of wheat grain Zn and Fe, identification of as many causal loci as possible is imperative ( Tong et al, 2020 ). In recent years, diverse bi-parental populations have been used to identify quantitative trait locus/loci (QTL) associated with grain Zn (GZnC) and Fe concentrations (GFeC) in common wheat and its relative species ( Tong et al, 2020 ; Gupta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%